Nutrition for infants and children - Jackson, Lisa.; Meridian Education Corporation; Films for the Humanities & Sciences (Lawrenceville, NJ : Meridian Education Corporation, 2006)
Explains the importance of good nutrition for newborns, infants, toddlers, and preschool-aged children and provides advice for parents and caregivers. Examines the beneficial effects of good nutrition and physical activity on children's growth and development. Discusses topics such as the relative merits of breastfeeding and bottle feeding, food allergies, and special dietary preferences like vegetarianism.
There are four chapter or topic includes in the video which are : feeding your infant, feeding your toddler, feeding your preschool-aged child and stay active.
Editor, Lisa Jackson ; music, David Giuffre ; graphics, Larry Petraccaro.
Narration: Suzanne Weintraub.
Keywords: Infants -- Nutrition; Children -- Nutrition; Nutrition